Estudo computacional das propriedades termodinâmicas e dinâmicas da água sobre superfícies bi-dimensionais com corrugações - Rossatto, Rafael Gustavo (2024)
The study of fluid dynamics on nanostructured surfaces is crucial due to the distinct behavior observed at this scale compared to the macroscopic world. This understanding is essential for various technological applications that benefit from nanomaterials, such as self-cleaning surfaces and more efficient energy storage systems. While many studies have been conducted on smooth surfaces, nature often presents surfaces with some degree of imperfection, necessitating a deeper theoretical investigation into these systems and solidliquid interactions. To accomplish this, we will employ molecular dynamics (MD) techniques to simulate water transport on nanostructured surfaces, comparing smooth and corrugated states. Our aim is to understand how water molecules move on different substrates and to gain both qualitative and quantitative insight into the relationship between the contact angle of liquid molecules and surface imperfections. Our results have shown that surface corrugation has a significant impact on these properties. For example, we observed a transition from the hydrophilic to hydrophobic regime and vice versa with the introduction of surface corrugations. Furthermore, we discovered that surface undulation affects transport properties such as diffusion and viscosity, revealing important correlations between these phenomena.